Technological and Scientific Mapping of New Corrosion Inhibitor Compositions - Morais, Williams Raphael (2018)
Corrosion can be defined as the deterioration that occurs when a material (usually a metal) reacts with its environment, leading to the loss of its properties. Corrosive processes cause great problems in the most varied activities, for example in the chemical and petroleum industries, transportation and communication, dentistry, medicine and works of art such as monuments and sculptures. In this sense, the present article aimed to perform a survey of the types of corrosion inhibitors, their applicability, main substances and / or materials applied for this purpose. Thus, searches were made on bases of a technological nature and on scientific production bases. With respect to the Patent Classification (IPC), 20 different codes were recovered. The mapping showed that studies on corrosion inhibitors have grown over the years, especially in the last 10 years.